Shared languages and teaching contextualization: an analysis in the geometry items of enem - Rodrigues, João Gabriel Macedo (2021)
This research aims to analyze how the geometry issues in the National High School Exam (ENEM) of 2018/2019 address shared languages ​​and the contextualization of teaching in the light of the Common National Curricular Base (BNCC) and the Curricular Parameters National High School (PCN +). Seeking this understanding, for the development of this work, a descriptive and analytical documentary research was carried out. 26 items of flat and spatial geometry were listed, whose cataloging of the items was divided into two blocks, one of which is questions that explicitly arise from geometry and the other with questions that are not shown to be of geometry. The results show that the questions seek from the students not only to evaluate the scientific knowledge itself, but also to evaluate the students' competences in relation to understanding, application, contextualization and resolution method. This corroborates what has been discussed about the quality of mathematics education developed in public schools, which must be seen in a specific, necessary and guided way in the educational policies of our country.